ECOLOGICAL MESSAGE IN THE QUR’AN: ANALYSIS AND REFLECTION ON QS. AL-NABĀ’ (78): 9-11 IN THE TAFSIR SALMAN ITB BANDUNG - Hasanah, Hofifatun (MUSHAF: Jurnal Tafsir Berwawasan Keindonesiaan, 2024)
The Qur’an has a strong ecological dimension, where many verses discuss nature, the earth, and the universe. QS. Al-Naba’s: 9-11 implies ecological principles such as the balance between activity and rest, environmental protection, and ecosystem sustainability. Tafsir Salman ITB provides an in-depth interpretation of the relationship between divine revelation and modern ecological principles. In general, this study aims to explore and analyze the ecological dimensions contained in QS. Al-Naba’s: 9-11 through the approach of Tafsir Salman. Specifically. Specifically, this study aims to identify the ecological values in QS. Al-Naba’: 9-11 and their relevance to ecosystem balance, analyze Tafsir Salman's interpretation of these verses in the context of modern ecology, explore Tafsir Salman's contribution in connecting the ecological message of the Qur'an with the basic principles of the ecosystem, explore the relevance of Tafsir Salman’s views in building ecological awareness based on the principles of the Qur’an, and provide a deeper understanding of the relationship between divine revelation and modern science related to environmental issues. This study uses a qualitative-descriptive approach with an interpretation analysis method. The focus of the study is on the ITB Salman Interpretation related to QS. Al-Naba’s: 9-11, with an analysis of ecological principles such as balance, adaptation, and sustainability. This study is expected to contribute to building ecological awareness based on the principles of the Qur’an. This understanding is important to connect modern science and the values of revelation in maintaining environmental sustainability. The results of this study indicate that QS. Al-Naba’s: 9-11 reflects ecological principles that include the cycle of life, protection at night, and productivity during the day. Salman’s interpretation emphasizes that night is a time of recovery and security, while day is a time of productivity and energy balance. The day and night cycle is an ecological system that supports the sustainability of life on Earth. This interpretation emphasizes the importance of human awareness in maintaining the natural rhythm of the ecosystem for sustainable environmental balance.